Effects of nano graphene particles on surface roughness and cutting temperature during MQL milling of AISI 430 stainless steel - Uysal, Alper (CARL HANSER VERLAG, 2018)
Stainless steel is hard-to-cut due to its material specifications and many problems are encountered machining it. Nevertheless, stainless steel is frequently preferred in industry and its use increases. In this experimental study, the machining of AISI 430 ferritic stainless steel under dry, MQL. (minimum quantity lubrication) and nanofluid MQL. milling conditions was investigated. Nanofluids were prepared by adding 1 wt.-% and 2 wt.-% nano graphene to commercial vegetable cutting fluid. In these experiments, uncoated WC (tungsten carbide) and TiN (titanium nitride) coated WC cutting tools were used and MQL. flow rates were selected as 20 ml x h(-1) and 40 ml x h(-1). Surface roughness and cutting temperatures were measured and the effects of using nanofluid, MQL flow rate, and TiN coated cutting tools were specified. According to the experimental results, the MOL method was shown to be beneficial for reducing cutting temperature and surface roughness values and the nanofluid MQL yielded minimum values. Moreover, TiN coating and an increased MQL. flow rate decreased cutting temperature and surface roughness.
Keywords: MQL; nanofluid; nano graphene; milling; surface roughness; cutting temperature; AISI 430; MINIMUM QUANTITY LUBRICATION; NANOLUBRICATION; MORPHOLOGY; AL6061-T6; FLUIDS; Materials Science